Manuel Burga, edit., Historia de América Andina. Formación y apogeo del sistema colonial" Vol. 3, Universidad Andina Simón Bolívar, Sede Ecuador/Libresa, Quito, 2002, 426 pp. (Procesos. Revista Ecuatoriana de Historia, 2002)
s.r.